PENGARUH HARGA KARET TERHADAP TINGKAT KESEJAHTERAAN MASYARAKAT DI DESA BERINGIN DALAM KECAMATAN RAMBANG KUANG KABUPATEN OGAN ILIR SUMATERA SELATAN - Mudzakir ilyas; Fitria; Zannuba Arifa Ratih (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2023)
Introduction : The price of rubber in the village in experiencing fluctuations and people's income becomes unstable. If the selling price of rubber is rising, the income of farmers will increase, and vice versa if the selling price of rubber decreases, the income of the community will also decrease. Mettod : This research uses quantitative research methods. with Variable (X) is the Effect of Rubber Prices, while Variable (Y) is the Welfare Level. The population taken is 341 families. The sample in this study amounted to 80 families. Data analysis used in this study includes: Normality test, T test, Simple Regression Analysis, Coefficient of Determination (R Square). Conclusion and suggestion: Based on data from the test results of the Coefficient of Determination (R2) it was found that rubber prices had a 47% influence. This states that the price of rubber does not affect the level of welfare of rubber farmers. This is also proven from the results of the t test where it was found that the value of tcount < ttable is 1.961 < 1.99085 and a significant value of 0.053 > 0.05. Then Ho is accepted and H1 is rejected. So it means that it can be concluded that the hypothesis states the results of the variable "Rubber Prices (X) have no effect on the variable Level of Welfare of Society (Y)".